The Effectiveness of Intervention of Treatment Based on Acceptance-Commtment Therapy with drug control on the Rate of Parent, s Acceptance of Autistic Children and Their Denial-Defense Mechanism - Maryam Khorasani Dehshotoran (Journal of Global Pharma Technology, 2017)
The purpose of this study was to measure the efficiency of intervention of treatment based on acceptance-commitment therapy (ACT) with drug control on the rate of parent,s acceptance of autistic children and their denial defense mechanism. The present study consisted of pre-test and post test with control group. The subjects of this study were comprised of Atypical Children Centers in Esfahan in the first three months in 1394. Based on convenient sampling, 40 women, having at least one autistic child, were selected. The instruments of the study were Defense Styles Questionnaire (DSQ) and Acceptance and Action Questionnaire-2 (AAQ-2) and also Ways of Coping Questionnaire (WOCQ). Participants were randomly classified in to control and experimental groups. Also Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Automatic Thoughts Questionnaire(ATQ) were used for mental health assessment in depression-anxiety domain of participants. The experimental group had 8 training sessions, each 90 minutes, and participants were exposed to commitment acceptance therapy. Defense Styles, Acceptance and Action and Ways of Coping Questionnaire were applied again for two groups. The results of the study illustrate that maximal and minimal average number of coping strategy was for avoidant/ escap. And the dominant defense mode in mother’s experimental group was with regard to undeveloped mode. The result of covariance analysis revealed that acceptability of mothers being under the treatment of commitment- acceptance therapy significantly increased (p=0.032<0.05). Whereas there were on significant differences between the scores of mothers experiencing commitment domain in both groups (p=0.147>0.05). Based on the findings, it can be conclude that commitment acceptance therapy had positive effects on the increase of the level of mothers acceptance having auutistic children and with regard to the decrease of eruptional/denial fact in parents, it increased the improvement of the adaptation and family relationship.Keywords: autism, Denial defense machanism, Acceptance commitment therapy.